Gait Characteristics and Development in Pediatric Populations With Visual Disorders: Where Do We Stand and Where Are We Going? - Holly Bradley; Beth A. Smith
Introduction: Vision plays an important role in walking development. Understanding gait characteristics and development in infants and children with visual disorders is crucial to identify early walking impairment and promoting optimal motor performance. We aimed to identify typical gait patterns and differences between infants and children with visual disorders and their sighted peers, and how these change over time, identifying key research gaps in this area. Methods: A search of three databases identified 1,531 papers, of which eight met inclusion criteria. Results: Children who are blind showed differences in gait compared to peers with low vision or full sight. Differences were identified across age groups with slower walking, postural, head, and trunk position alterations and uncoordinated and reduced upper limb swing motions observed in children with blindness. Discussion: We identified three macro areas of interest related to gait characteristics in children with visual disorders: (1) and (2) compensation mechanisms of limbs, and (3) probing the environment. In general, children who are blind also showed the use of a wider base of support, more external rotation of the feet, and fewer steps taken per minute. There are no studies reporting gait characteristics in the early stages of walking development, scarcity of longitudinal investigations, and studies using different variables to measure gait. The lack of such evidence prevented the establishment of gait development trajectories over time in pediatric populations with visual disorders. Implications for Practitioners: This review is the first to summarize existing knowledge of gait characteristics in children with visual disorders, advancing our understanding regarding the key differences in gait patterns that are observed in this population. Information gathered in this work can help inform future studies and practitioners in this field, enhancing decision-making processes to support walking development and promoting increasing knowledge of gait progresses in infants and children with visual disorders.